POTENTIALITY AND HUMAN EMBRYOS - Lizza, John P. (Bioethics, 2007)
Consideration of the potentiality of human embryos to develop characteristics of personhood, such as intellect and will, has figured prominently in arguments against abortion and the use of human embryos for research. In particular, such consideration was the basis for the call of the US President's Council on Bioethics for a moratorium on stem cell research on human embryos. In this paper, I critique the concept of potentiality invoked by the Council and offer an alternative account. In contrast to the Council's view that an embryo's potentiality is determined by definition and is not affected by external conditions that may prevent certain possibilities from ever being realized, I propose an empirically grounded account of potentiality that involves an assessment of the physical and decisional conditions that may restrict an embryo's possibilities. In my view, some human embryos lack the potentiality to become a person that other human embryos have. Assuming for the sake of argument that the potential to become a person gives a being special moral status, it follows that some human embryos lack this status. This argument is then used to support Gene Outka's suggestion that it is morally permissible to experiment on ‘spare’ frozen embryos that are destined to be destroyed.